Motivation Factors for Adopting Building Information Modeling (BIM) in Iraq - Hatem, W. A.; Abd, A. M.; Abbas, N. N. (Engineering, Technology & Applied Science Research, 2018)
Building information modeling (BIM) is an integrated and comprehensive system including whatever is related to a construction project and its stages. It represents a unified database for all project data through which project documents are available to all stakeholders. This paper evaluates the factors driving the adoption of BIM in Iraqi construction projects in different ministries and adopts quantitative approach to collect data by using a questionnaire survey specially prepared for this purpose which was distributed to experts in the ministries of the Iraqi construction sector. Returned data were subjected to proper statistical analysis. Results showed that the highest motivation for BIM application is to include it in the educational curricula, raise awareness through courses and workshops and contracting with international experts with experience in BIM field.